2020
DOI: 10.7717/peerj.9501
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional microbial diversity of sandy soil under cropland and grassland

Abstract: Background Land use change significantly alters soil organic carbon content and the microbial community. Therefore, in the present study, the effect of changing cropland to grassland on structural and functional soil microbial diversity was evaluated. The specific aims were (i) to identify the most prominent members of the fungal communities and their relevant ecological guild groups; (ii) to assess changes in the diversity of ammonia-oxidizing archaea; (iii) to determine the relationships between microbial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Mortierella species, representing plant growth-promoting abilities (Figure 1) are isolated from the agricultural soils (bulk soil, rhizosphere soil) (Table 1). Recent studies of rhizosphere soils or endophytes of various plant species proved that the presence of Mortierella provides a higher resistance at soil-borne pathogens or/and improve plant growth (Table 2) [9,33,64,65]. Recent studies of rhizosphere soils or endophytes of various plant species proved that the presence of Mortierella provides a higher resistance at soil-borne pathogens or/and improve plant growth (Table 2) [9,33,64,65].…”
Section: Plant Growth-promoting Abilities Of Mortierella Speciesmentioning
confidence: 99%
“…Mortierella species, representing plant growth-promoting abilities (Figure 1) are isolated from the agricultural soils (bulk soil, rhizosphere soil) (Table 1). Recent studies of rhizosphere soils or endophytes of various plant species proved that the presence of Mortierella provides a higher resistance at soil-borne pathogens or/and improve plant growth (Table 2) [9,33,64,65]. Recent studies of rhizosphere soils or endophytes of various plant species proved that the presence of Mortierella provides a higher resistance at soil-borne pathogens or/and improve plant growth (Table 2) [9,33,64,65].…”
Section: Plant Growth-promoting Abilities Of Mortierella Speciesmentioning
confidence: 99%
“…Microbes can help to maintain the fertility of soil and in the decomposition of organic matter, and the addition of beneficial bacteria into soil ecosystems will enhance the resistance of plants to disease [8,9]. The microbial community is one of the key factors affecting the growth of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are known to affect soil fungal community structure and function. It has been suggested that the soil fungal community composition at both global and regional scales is mainly driven by abiotic factors such as soil C:N ratio (Lauber, Strickland, Bradford, & Fierer, 2008;Thomson et al, 2015), pH (Dumbrell, Nelson, Helgason, Dytham, & Fitter, 2010;Sun et al, 2016;Tedersoo et al, 2015), soil organic carbon content, soil texture, overall climatic conditions, and land use (Creamer et al, 2016;Frac, Jerzy, Bogusław, Karolina, & Małgorzata, 2020;Sun et al, 2016;Thomson et al, 2015). Additionally, at more local scales, plant species identity (Hannula, Ma, Pérez-Jaramillo, Pineda, & Bezemer, 2020) and agricultural practices (Bender, Wagg, & van der Heijden, 2016;Frąc et al, 2018;Oehl, Laczko, Oberholzer, Jansa, & Egli, 2017;Rillig et al, 2016) have been identified as important factors affecting fungi.…”
Section: Introductionmentioning
confidence: 99%